Self-report of Quezon City-Hall of Justice and Regional Trial Court-Manila prosecutors' communication behavior during investigative interviewing of alleged sexually abused children - Mercado, Amor David R. (2007)
This master's thesis, titled Self-Report of Quezon City-Hall of Justice and Regional Trial Court-Manila Prosecutors' Communicative Behavior during Investigative Interviewing of Alleged Sexually Abused Children, focused primarily on examining and understanding the communication behavior of selected prosecutors while interviewing children who are alleged to have been abused sexually. In general, this study aimed to describe the QC-Hall of Justice and RTC Manila prosecutors' communication behavior when they conduct investigative interviewing of alleged sexually abused children. Specifically, this study aimed to achieve the following objectives: 1. To identify the communication styles of QC-Hall of Justice and RTC-Manila prosecutors' exhibit during investigative interviewing with alleged sexually abused children. 2. To identify the question types and utterances posed by prosecutors of QC-Hall of Justice and RTC Manila in the investigative interviewing of children who are alleged to have been sexually abused. 3. To identify the content subsumed in the questions being asked of the alleged sexually abused children by the prosecutors. This study was undertaken using, primarily, the qualitative interview, and, secondarily, a questionnaire called Self-Perception Communicative Behaviors Questionnaire. Ten (10) prosecutors were purposively chosen. The results and analysis of the data yielded several findings. Results showed that QC-Hall of Justice and RTC-Manila prosecutors used developmentally appropriate communicative behaviors and conducted investigative interviewing that was also developmentally appropriate to alleged sexually abused children. Specifically, this study on the communication behavior of prosecutors doing investigative interviewing of children who are alleged to have been sexually abused led to the following conclusions: 1. Prosecutors use utterances such as invitations, directive, option-posing, suggestive and non-substantive and ask questions that are open-ended, focused, specific and, most especially, leading. The prosecutors adjust the content, manner and language of questioning to the culture and level of understanding of the child. 2. The prosecutors use developmentally appropriate investigative interview protocols such as establishing rapport, assessing the child's development, establishing incident details, and closing the interview. Prosecutors have various communication styles (as per Norton, 1976): friendly, attentive, animated, relaxed, dramatic, open, contentious, and dominant. 3. The content of the question and the manner in which a question is asked are not misleading or confusing, are phrased in an appropriate language and are not annoying, harassing, intimidating, and offensive. The questions are not structured or sequenced in a way that is intimidating, harassing, confusing, annoying or misleading. This study offered knowledge and insights to further our understanding of legal communication. Its findings had important implications on legal processes involving legal practitioners who are handling cases of sexually abused children.